Association between duration of exclusive breastfeeding and nursing mothers' self-efficacy for breastfeeding - Gécica Gracieli Wust de Moraes; Marialda Moreira Christoffel; Beatriz Rosana Gonçalves de Oliveira Toso; Cláudia Silveira Viera (SciELO, 2021)
ABSTRACT Objective: To verify the association of nursing mothers' self-efficacy for breastfeeding in the immediate postpartum period and six months after birth and obstetric and sociodemographic variables with the duration of exclusive breastfeeding. Method: Observational, longitudinal, prospective study which followed nursing mothers from the immediate postpartum period to the sixth month postpartum in a municipality in Southern Brazil. For data collection, a questionnaire with sociodemographic and obstetric variables and the scale Breastfeeding Self-Efficacy Scale - short form - were employed in the maternity ward and six months after birth. Inferential and descriptive statistics were employed. Results: A total of 158 nursing mothers have participated. The prevalence of exclusive breastfeeding in the sixth month was 36.70%, out of which 77.34% have presented a high self-efficacy score. Sociodemographic factors had a negative impact on exclusive breastfeeding. Conclusion: High levels of self-efficacy favor exclusive breastfeeding; however, such factor, in isolation, is not decisive for exclusive breastfeeding. Self-efficacy should be identified during the pre-natal period through mothers' employment and marital status data to promote preventive actions against early weaning.